Dynamic Modeling of Multi-category Jointing for the Autonomous-railRapid Tram and Real Vehicle Validation - HUANG Ruipeng; YUAN Xiwen; HU Yunqing; ZHANG Xinrui; ZHANG Sha; LI Xiaoguang (Kongzhi Yu Xinxi Jishu)
Autonomous-rail rapid tram replaces traditional steel wheels with rubber tires, and uses machine vision to track the central virtual track line to control vehicle motion. In order to iteratively optimize and reduce the lateral deviation of the precision lane keeping control system, a 35 m train dynamic model was built in this paper to meet the characteristics of autonomous-rail rapid tram such as tire-ground coupling and multi-group flexible articulating. Through the Matlab / Simulink dynamic model simulation test, it is verified that the dynamic model can show fast track driving of an autonomous-rail rapid tram in a narrow gauge of an old city and precise docking of a small platform gap (the deviation is controlled at 8~12 cm).